Nerve-sparing vs. non-nerve-sparing open radical prostatectomy: correlations between International Index of Erectile Function and corpus cavernosum electromyography - Vojinov, Saša; Jeremić, Dimitrije; Levakov, Ivan; Bogdanović, Jovo; Popov, Mladen; Stojanović, Stevan; Govedarica, Srdjan (Vojnosanitetski pregled, 2025)
Background/Aim. Erectile dysfunction (ED) increases with age, and the importance of sexual health has become more widespread in therapeutic practice. The aim of this study was to evaluate the correlation between subjective and objective measures of ED in patients undergoing nerve-sparing vs. non-nerve-sparing open radical prostatectomy for localized prostate cancer. Methods. This prospective controlled study included 50 patients with diagnosed prostate cancer and normal preoperative erectile function (EF). Patients were divided into nerve-sparing (n = 25) and non-nerve-sparing (n = 25) groups. EF was assessed preoperatively and at six months using the International Index of Erectile Function (IIEF) questionnaire, while corpus cavernosum electromyography recorded spontaneous smooth muscle activity. Statistical analysis included paired t-tests and Spearman’s correlations. Results. Postoperative IIEF scores declined significantly in both groups (nerve-sparing: 22.04 ± 2.10 to 17.87 ± 3.83, p < 0.001; non-nerve-sparing: 21.67 ± 2.64 to 6.42 ± 1.51, p < 0.001). Bilateral nerve-sparing preserved superior EF compared to unilateral preservation (19.87 ± 2.80 vs. 14.13 ± 2.42, p < 0.001). No significant correlation was found between corpus cavernosum electromyography parameters (amplitude, mean wave, phase reversals) and IIEF scores (p > 0.05). Conclusion. Nerve-sparing open radical prostatectomy, particularly bilateral techniques, significantly reduces ED severity. However, corpus cavernosum electromyography did not correlate with patient-reported outcomes, suggesting its limited standalone utility in postoperative ED assessment.